THE DYNAMICS OF REGULATION ON CHANGES IN THE LEGAL FORM OF STATE-OWNED ENTERPRISES ACCORDING TO ARTICLE 92 OF LAW NO. 19/2003: A LITERATURE ANALYSIS OF STRATEGIC STEPS FOR CONVERTING PERJAN INTO PERUM OR PERSERO AND THE IMPLICATIONS FOR OPERATIONAL EFFICIENCY AND GOVERNMENT COMPLIANCE - Shohib Muslim; Karman Karman (CV. Adiba Aisha Amira, 2026)
This article analyses the dynamics of the regulation of changes in the legal form of state-owned enterprises based on Article 92 of Law No. 19 of 2003, focusing on the strategic steps for converting a Government Agency (Perjan) into a Public Company (Perum) or Limited Liability Company (Persero) as stipulated in Government Regulation No. 45 of 2005. Through a normative juridical approach and content analysis of laws, government regulations, legal journals, and empirical case studies such as PT Pos Indonesia, Pegadaian, and PT KAI, the study identifies structured procedures ranging from feasibility studies, proposals from the Minister of State-Owned Enterprises to the President, issuance of Government Regulations, appointment of organs, to the separation of assets and PSO accounting. The results show that the conversion significantly improves operational efficiency with an average ROA increase of 5-10%, a 20-30% reduction in structural costs, and business diversification, accompanied by strengthened government compliance through the GMS, BPK/OJK supervision, and separate PSO compensation contributing Rp150 trillion in dividends to the state budget in 2025. Strategic implications include the transformation of SOEs from a bureaucratic model to competitive corporate entities, although the challenges of legacy debt and political intervention require mitigation through the independence of the board of commissioners and holding companies, as per the current trend in January 2026. Overall, Article 92 has proven effective as a catalyst for reform, with recommendations for amendments to government regulations for the integration of AI digitalisation in pre-conversion assessments, mass human resource training, and the acceleration of the conversion of residual Perum for national economic synergy. This research contributes theoretically to the study of state economic law and practically to the Ministry of State-Owned Enterprises in optimising the strategic role of state-owned enterprises in accordance with Article 33 of the 1945 Constitution.